2019
DOI: 10.1002/bit.27121
|View full text |Cite
|
Sign up to set email alerts
|

Expanding targeting scope, editing window, and base transition capability of base editing in Corynebacterium glutamicum

Abstract: CRISPR/Cas9‐guided cytidine deaminase enables C:G to T:A base editing in bacterial genome without introduction of lethal double‐stranded DNA break, supplement of foreign DNA template, or dependence on inefficient homologous recombination. However, limited by genome‐targeting scope, editing window, and base transition capability, the application of base editing in metabolic engineering has not been explored. Herein, four Cas9 variants accepting different protospacer adjacent motif (PAM) sequences were used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 41 publications
(107 reference statements)
1
45
1
Order By: Relevance
“…The low efficiency of triple-site editing could be possibly caused by the lower amount of the base editor at each locus than those targeting single loci. And a developed system with expanding targeting scope, editing window, and base transition capability was further constructed in C. glutamicum by the same group ( Wang et al, 2019 ).…”
Section: Regulation Of Gene Expression By Crispr/cas Toolboxmentioning
confidence: 99%
“…The low efficiency of triple-site editing could be possibly caused by the lower amount of the base editor at each locus than those targeting single loci. And a developed system with expanding targeting scope, editing window, and base transition capability was further constructed in C. glutamicum by the same group ( Wang et al, 2019 ).…”
Section: Regulation Of Gene Expression By Crispr/cas Toolboxmentioning
confidence: 99%
“…After the base editing procedure, DNA sequencing showed that spacers HexR ( Supplementary Figure S5 ), PA2018 ( Figure 4A ), HexR-2 and HexR-3 ( Figure 5B ) exhibited significantly higher mutation efficiencies than the original spacers HexR-5, PA2018-2, and HexR-4. To minimize the motif preference of APOBEC1 or the disruption of off-target effects, the design of the 20-bp spacer with a NGG or NG PAM for gene inactivation should be assessed by base editing designing tools ( Xiao et al, 2014 ; Hwang et al, 2018 ; Wang et al, 2019 ) in an effort to overcome this potential limitation ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The element UGI was fused to the C-terminus of APOBEC1-XTEN- eSpCas9pp D10A in pSEVA-Module 4, giving rise to pSEVA-Module 6. pSEVA-Module 6 was named pSEVA6BE, which was used as the template for the construction of following base editing plasmids ( Supplementary Table S2 ). All of the base editing spacers ( Supplementary Table S4 ) used in this study were designed and analyzed by CasOT ( Xiao et al, 2014 ), gBIG ( Wang et al, 2019 ), or BE-Designer ( Hwang et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the cas9 copy number has been reduced through genomic integration, and weak promoters including P tuf have been used to develop the genome editing tool of C. glutamicum [12]. A modi ed Cas9 recognizing the 5′-NG sequence as the PAM sequence has been recently reported to recognize more target DNA sequences during genome engineering in C. glutamicum [23].…”
Section: Introductionmentioning
confidence: 99%